When should retirees tap their home equity? - Christoph Hambel; Holger Kraft; André Meyer-Wehmann (Leibniz Institute for Financial Research SAFE, 2020)
This paper studies a household's optimal demand for a reverse mortgage. These contracts allow homeowners to tap their home equity to finance consumption needs. In stylized frameworks, we show that the decision to enter a reverse mortgage is mainly driven by the differential between the aggregate appreciation of the house price and principal limiting factor on the one hand and the funding costs of a household on the other hand. We also study a rich life-cycle model that can explain the low demand for reverse mortgages as observed in US data. In this model, we analyze the optimal response of a household that is confronted with a health shock or financial disaster. If an agent suffers from an unexpected health shock, she reduces the risky portfolio share and is more likely to enter a reverse mortgage. On the other hand, if there is a large drop in the stock market, she keeps the risky portfolio share almost constant by buying additional shares of stock. Besides, the probability to take out a reverse mortgage is hardly affected.
Keywords: D14; E21; G11; G21; J14; R21; 330; reverse mortgage; consumption-portfolio decisions; optimal stopping; biometric risks; financial disasters